The scale and evolutionary significance of horizontal gene transfer in the choanoflagellate Monosiga brevicollis - Yue, Jipei (BioMed Central, 2013)
BACKGROUND: It is generally agreed that horizontal gene transfer (HGT) is common in phagotrophic protists. However, the overall scale of HGT and the cumulative impact of acquired genes on the evolution of these organisms remain largely unknown. RESULTS: Choanoflagellates are phagotrophs and the closest living relatives of animals. In this study, we performed phylogenomic analyses to investigate the scale of HGT and the evolutionary importance of horizontally acquired genes in the choanoflagellate Monosiga brevicollis. Our analyses identified 405 genes that are likely derived from algae and prokaryotes, accounting for approximately 4.4% of the Monosiga nuclear genome. Many of the horizontally acquired genes identified in Monosiga were probably acquired from food sources, rather than by endosymbiotic gene transfer (EGT) from obsolete endosymbionts or plastids. Of 193 genes identified in our analyses with functional information, 84 (43.5%) are involved in carbohydrate or amino acid metabolism, and 45 (23.3%) are transporters and/or involved in response to oxidative, osmotic, antibiotic, or heavy metal stresses. Some identified genes may also participate in biosynthesis of important metabolites such as vitamins C and K12, porphyrins and phospholipids. CONCLUSIONS: Our results suggest that HGT is frequent in Monosiga brevicollis and might have contributed substantially to its adaptation and evolution. This finding also highlights the importance of HGT in the genome and organismal evolution of phagotrophic eukaryotes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1471-2164-14-729) contains supplementary material, which is available to authorized users.